Aggregometry in the settings of thrombocytopenia, thrombocytosis and antiplatelet therapy. (3rd October 2018) - Podda, GianMarco; Scavone, Mariangela; Femia, Eti Alessandra; Cattaneo, Marco
Abstract: A variety of laboratory tests have been developed, which can diagnose a number of both congenital and acquired disorders of platelet function. Many tests of platelet function measure the ability of platelets to adhere to each other, forming platelet aggregates, which represent the major constituents of hemostatic plugs and of arterial thrombi. Light transmission aggregometry (LTA) is still considered the gold standard of platelet aggregation tests, but other platelet aggregation-based tests are also available. Among them, the flow cytometry-based methods may be more convenient than LTA for the study of patients with very low or very high platelet counts. The use of platelet aggregation tests has also been advocated to monitor the treatment with antiplatelet agents (mostly the P2Y12 antagonist clopidogrel) of patients with thrombotic arterial occlusions, with the aim of improving their efficacy and safety. However, randomized clinical trials failed to show any advantage of this strategy; as a consequence, international guidelines now recommend against laboratory monitoring of antiplatelet therapy.